AN APPLICATION OF DISTRIBUTION REQUIREMENTS PLANNING (DRP) FOR PRODUCT DISTRIBUTION SCHEDULING IN A FOOD INDUSTRY COMPANY - Basuki, Mahmud; Farisi, Noval Al; Armijal, Armijal (LPPM Universitas Jambi, 2026)
This research aims to develop a product distribution schedule that meets customer demand in a timely manner while optimizing the company’s total distribution costs. This research employs a quantitative descriptive approach using a case study design at PT Tom Burger Group, a fast-food company specializing in burger buns. Data were collected through direct observation, semi-structured interviews, and company documentation, including demand and inventory data over a 10-day period. The Distribution Requirements Planning (DRP) method was applied as the main analytical tool, involving demand forecasting, inventory analysis, and distribution scheduling calculations to determine optimal delivery plans and total distribution costs. The results indicate that the implementation of DRP improves the efficiency of distribution scheduling and reduces unnecessary distribution costs. Furthermore, improved planning contributes to increased customer satisfaction by ensuring timely product availability in accordance with market demand. Based on the DRP calculations, Tawar bread has the lowest total distribution cost, with 37 deliveries per year and a total cost of IDR 4,015,240. Similarly, Mini Burger, Premium Burger, and Burger bread also require 37 deliveries annually but result in different total costs due to variations in holding costs. In contrast, Jhon bread has the highest frequency of deliveries, with 111 deliveries per year and a total cost of IDR 17,804,400. The findings highlight the importance of structured, data-driven distribution planning in improving operational performance. This study is expected to support managerial decision-making in product distribution and contribute to the development of knowledge in industrial engineering.